Peran Pendidikan Terhadap Perubahan Strategi Perjuangan Perempuan pada Masa Penjajahan - Yuliati, Yuliati; Ismail, Akhmat Safiudin (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
The purpose of writing the article is to discuss the role of women in the nation’s struggle during the colonial period before and after the existence of educational institutions. The study uses the library research method with data sources from various existing papers. Data analysis uses descriptive qualitative. Before there was ethical politics in the field of education, women’s struggles were carried out through their involvement in various wars or resistance against colonialists. Women struggle to hold weapons in regional wars. Educational institutions that were founded as a policy of retribution provide women with the opportunity to fight through education and organization. Efforts to spread the spirit of nationalism and struggle are carried out through organizations and writing in the mass media.